PREVALENCE OF GASTRO- INTESTINAL PARASITES OF HORSES IN BAGHDAD AREA ‎ - Y. Yakoob, A.; H. Issa , W.; l. Altaif, K. (The Iraqi Journal of Veterinary Medicine, 1988)
A study on the prevalence of gastrointestinal parasites of horses in Baghdad area extending over a period of one year , revealed two small peaks in worm egg counts , one in spring and the other in autumn and treatment routines should be based on this information. During the hot and dry summer months of Iraq, helminth infection was at low level.Faecal culture for larvae and their identification indicated the predominance of small red worm infection in the horses.